Calidad del agua para riego en la producción del cultivo de banano (Musa AAA). - Martínez Castro, José Luis (2024)
The quality and quantity of water are measures that make up the environmental system, intended for the calculation of environmental sustainability, including indicators recognized and approved by the UN to specify sustainable development. To determine the quality of water, analysis must be done in the laboratory, studying its chemical, physical and biological properties. In the province of Los Ríos, Ecuador, there is a growing complication due to the decrease in the quality of water used for irrigation in banana production, affecting the productivity and quality of the fruit. Therefore, this work is of vital importance due to its theoretical content, since the banana industry is an economic pillar for the province and Ecuador. In this way, this work aimed to analyze the relationship between the quality of irrigation water and banana production systems in the province of Los Ríos, Ecuador. Carried out by collecting information from scientific articles, websites, Google Scholar and virtual libraries. Taking into account that the quality of water for irrigation is crucial in Musa AAA banana production systems, since it directly influences the performance and health of the plants, and that contaminants can cause diseases in banana plants, weakening them and reducing their productivity. Concluding that, the quality of water for irrigation is essential in banana production, and the use of contaminated water causes diseases, affecting the quality and quantity of the harvest.